Developing Reading Skill among Iraqi ENGLISH AS FOREIGN LANGUAGE learners - Muhammad Ismail; Sheimaa marza (مجلة الآداب, 2023)
The main thrust of the present study was to improve Iraqi English as foreign language learners’ speaking. To this end, 30 ENGLISH AS FOREIGN LANGUAGE learners were selected as the participants of the study. All participants took the pretest followed by 25 ninety-minute sessions in which the learners presented their lectures (totally 9 lectures) followed by the challenging questions that they had to answer and the correction feedback in terms of vocabulary, structure, collocation, etc. Moreover, every three lectures followed by taking a progressive test, the posttest and the delayed posttest. Having followed the repeated measure ANOVA, the researcher put the data into SPSS 22 and analyzed it in terms of both descriptive and inferential statistics. It was found that teaching Reading through the tenets of sociocultural theory is influential and equally effective for all participants irrespective to their level or age. The results of the study indicated that presenting lecture improves the learners’ Reading development, consciousness-raring regarding learning processes and learning linguistic items, collaboration, autonomy and motivation. It was also pointed out that learning is not a straightforward transmission of knowledge provided by the teacher but a transformative and complex process for which learner’s agency, engagement and their co-construction of knowledge are crucial.